A self-repairing grouting material based on ureidopyrimidone, preparation method and application thereof
By using self-healing grouting materials based on ureidopyrimidone in coal mine tunnels, the problem of insufficient dynamic durability of the surrounding rock in the tunnel under high ground stress is solved, the self-repair and strength recovery of grouting materials are achieved, and the reliability of safe production of coal mines is improved.
Patent Information
- Application Number
- CN202410940309.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Deep mining of coal mines causes the tunnel to face high ground stress, anchor bolt breakage, support member failure and large deformation of surrounding rocks. The existing grouting materials lack dynamic durability in the continuous rheology and large deformation tunnel, resulting in the damage of the stone body.
Using a self-healing grouting material based on ureidopyrimidone, a monomer composed of 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine is mixed with lysine diisocyanate and dicyclohexylmethane diisocyanate, mixed polyol and composite catalyst are added, and ureidopyrimidone-polyol copolymer is prepared after reaction and drying, and mixed with self-healing accelerator and additives are mixed, and aluminate clinker is added to prepare a self-healing grouting material.
The material has an amphiphilic structure and an aromatic ring structure, which improves the water loss, water retention and interface bonding of the grouting material, and realizes self-healing characteristics through reversible dynamic hydrogen bonding, which improves the dynamic durability and strength recovery rate of the grouting material.
Smart Images

Figure CN118702457B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of mining engineering technology, and in particular to a self-repairing grouting material based on ureidopyrimidone, a preparation method and application thereof. Background Art
[0002] As the depth of coal mining increases, tunnels face problems such as anchor bolt breakage, support component failure, and large deformation of tunnel surrounding rocks under the superposition of high ground stress and strong mining, which seriously affect the safe production of coal mines. Grouting modification can actively modify the soft coal body, improve "integrity", enhance "strength performance", and control "deformability". However, in tunnels with continuous rheological large deformation, there are problems such as tunnel deformation leading to the destruction of grouting stone bodies and insufficient long-term dynamic durability. The long-term dynamic durability of grouting materials caused by cracking and damage due to tunnel deformation seriously affects the effect of grouting modification and is the most important constraint factor for grouting reinforcement of tunnel surrounding rocks. Therefore, it is urgent to develop self-repairing grouting materials suitable for large deformation coal tunnels in coal mines. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. The present application provides a self-repairing grouting material based on ureidopyrimidone, a preparation method and an application thereof, and a self-repairing grouting material
[0004] To achieve the above-mentioned object, according to the first aspect of the present application, a method for preparing a self-repairing grouting material based on ureidopyrimidone is proposed, comprising the following steps:
[0005] The monomers composed of 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine are added to a mixed solution composed of lysine diisocyanate and dicyclohexylmethane diisocyanate, and then mixed with a mixed polyol, and reacted at 90-100° C. for 50-60 minutes under a composite catalyst and a protective atmosphere, and then the reaction solution is filtered and dried to obtain a ureido pyrimidone-polyol copolymer; wherein the mass ratio of the monomer to the mixed solution is 3:2; the mass ratio of the composite catalyst to the monomer is 1:15; and the mass ratio of the mixed polyol to the monomer is 4:5;
[0006] In parts by mass, 7-10 parts of the ureidopyrimidone-polyol copolymer, 1-3 parts of the self-repairing accelerator and 5-15 parts of the auxiliary agent are added to 100 parts of the cementitious material, and the dry powder is stirred to obtain the self-repairing grouting material.
[0007] In some embodiments, in the monomer, the mass ratio of the 2-ureido-4[H]-pyrimidinone to the 4-dimethylaminopyridine is 4:1.
[0008] In some embodiments, in the mixed solution, the mass ratio of the lysine diisocyanate to the dicyclohexylmethane diisocyanate is 1:2.
[0009] In some embodiments, the mixed polyol comprises tetrahydrofuran diol and polypropylene glycol in a mass ratio of 1:3.
[0010] In some embodiments, the composite catalyst includes lithium chloride and 8-hydroxyquinoline copper in a mass ratio of 2:1.
[0011] In some embodiments, the self-repair accelerator includes 4-pyrimidone, triazole pyrimidone and trifluorophenylpyrimidine in a mass ratio of 2:3:1.
[0012] In some embodiments, the additives include, by weight, 1-5 parts of a reinforcing agent, 1-3 parts of a toughening agent, 1-2 parts of a water retaining agent, 1-3 parts of a coagulant, and 1-2 parts of a drag reducing agent.
[0013] In some embodiments, the cementitious material is aluminate clinker.
[0014] According to another object of the present application, a self-repairing grouting material based on urea-pyrimidone is proposed, which comprises, by weight, 7-10 parts of urea-pyrimidone-polyol copolymer, 1-3 parts of self-repairing accelerator, 5-15 parts of auxiliary agent and 100 parts of cementitious material; the cementitious material is aluminate clinker.
[0015] In some embodiments, the self-repair accelerator includes 4-pyrimidone, triazole pyrimidone and trifluorophenylpyrimidine in a mass ratio of 2:3:1.
[0016] In some embodiments, the additives include, by weight, 1-5 parts of a reinforcing agent, 1-3 parts of a toughening agent, 1-2 parts of a water retaining agent, 1-3 parts of a coagulant, and 1-2 parts of a drag reducing agent.
[0017] In some embodiments, the ureido-pyrimidone-polyol copolymer is prepared by adding monomers composed of 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine to a mixture of lysine diisocyanate and dicyclohexylmethane diisocyanate, and then adding the mixed polyol, reacting at 90-100° C. for 50-60 minutes in the presence of a composite catalyst and a protective atmosphere, and then filtering and drying.
[0018] According to another object of the present application, it is proposed to use the self-repairing grouting material described in any of the above embodiments in the self-repair of large deformation coal lanes in coal mines.
[0019] Compared with the prior art, this application has the following advantages:
[0020] In the present application, the prepared urea-pyrimidone-polyol copolymer, self-repairing promoter, reinforcing agent, toughening agent, water-retaining agent, coagulant and drag reducer are added to the aluminate clinker cementitious material to prepare a urea-pyrimidone-based self-repairing grouting material suitable for large deformation coal lanes in coal mines. The prepared urea-pyrimidone-polyol copolymer has an amphiphilic structure, which can improve the water loss reduction and water retention properties of the grouting material, and is beneficial to improving the solid performance of the grouting structure; and the urea-pyrimidone-polyol copolymer has an aromatic ring structure, which can form a π-π conjugation effect with the aromatic ring of the coal body, which is beneficial to improving the interfacial adhesion between the grouting material and the coal body.
[0021] In addition, in the composite grouting material in the present application, the ureido pyrimidone-polyol copolymer has multiple hydrogen bonds. When the material is damaged, the reversible dynamic hydrogen bonds will break before ordinary covalent bonds due to their weaker bond energy. Then, under certain conditions, these reversible dynamic hydrogen bonds can rebond on the fracture surface to repair the damage, showing self-healing properties.
[0022] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0024] Figure 1 This is a flow chart of a method for preparing a self-repairing grouting material based on ureidopyrimidone in one embodiment of the present application.
[0025] Figure 2 yes Figure 1 Detailed diagram of the process. DETAILED DESCRIPTION
[0026] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the embodiments of the present application include all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.
[0027] like Figure 1 As shown, in order to achieve the above-mentioned purpose, according to the first aspect of the present application, a method for preparing a self-repairing grouting material based on ureidopyrimidone is proposed, comprising the following steps;
[0028] S1: adding monomers composed of 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine to a mixed solution composed of lysine diisocyanate and dicyclohexylmethane diisocyanate, and then adding a mixed polyol, reacting at 90-100° C. for 50-60 minutes under a composite catalyst and a protective atmosphere, and then filtering and drying the reaction solution to obtain a ureido pyrimidone-polyol copolymer; wherein the mass ratio of the monomer to the mixed solution is 3:2; the mass ratio of the composite catalyst to the monomer is 1:15; and the mass ratio of the mixed polyol to the monomer is 4:5;
[0029] S2: In parts by mass, add 7-10 parts of urea-pyrimidone-polyol copolymer, 1-3 parts of self-repairing accelerator and 5-15 parts of auxiliary agent to 100 parts of cementitious material, and stir the dry powder to obtain the self-repairing grouting material.
[0030] Among them, S1 Figure 2 As shown, 15 parts of a monomer mixed with 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine in a mass ratio of 4:1 are weighed and added to 10 parts of a mixed solution; wherein the mixed solution is mixed with lysine diisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1:2; after the mixed solution and the monomer are mixed, auxiliary heating is performed to 35°C, stirring for 5 minutes to promote uniform mixing to obtain a uniform solution. 1 part of a composite catalyst is added to the obtained uniform solution, wherein the composite catalyst includes lithium chloride and 8-hydroxyquinoline copper in a mass ratio of 2:1, and then 12 parts of a mixed polyol is added, and the mixed polyol includes tetrahydrofuran diol and polypropylene glycol in a mass ratio of 1:3. Under the composite catalyst and protective atmosphere, the reaction is carried out at 90-100°C for 50-60 minutes, and then the reaction solution is filtered and dried to obtain a ureido pyrimidone-polyol copolymer.
[0031] In the present application, 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine are added to lysine diisocyanate and dicyclohexylmethane diisocyanate, and auxiliary heating is performed to promote uniform mixing, and then lithium chloride and 8-hydroxyquinoline copper composite catalyst are added, and then polytetrahydrofuran diol and polypropylene glycol are added, and the reaction is carried out at 90-100°C for 50 minutes under argon protection conditions, and the reaction is filtered and dried to prepare a ureido pyrimidone-polyol copolymer. The ureido pyrimidone-polyol copolymer has an amphiphilic structure, which can improve the water loss reduction and water retention properties of the grouting material, and is beneficial to improving the grouting solid performance; and the ureido pyrimidone-polyol copolymer has an aromatic ring structure, which can form a π-π conjugation effect with the aromatic ring of the coal body, which is beneficial to improving the interfacial adhesion between the grouting material and the coal body.
[0032] In step S2, Figure 2As shown, 7-10 parts of the urea-pyrimidone-polyol copolymer, 1-3 parts of the self-repairing accelerator and 5-15 parts of the auxiliary agent in step S1 are weighed and added to 100 parts of the cementitious material, and the mixture is mixed in a dry powder mixer for 20 minutes to obtain a self-repairing grouting material; wherein the self-repairing accelerator includes 4-pyrimidone, triazole pyrimidone and trifluorophenylpyrimidine in a mass ratio of 2:3:1; the auxiliary agent includes 1-5 parts of a reinforcing agent, 1-3 parts of a toughening agent, 1-2 parts of a water retaining agent, 1-3 parts of a coagulant and 1-2 parts of a drag reducer; the cementitious material in this embodiment is aluminate clinker.
[0033] Therefore, the present application adds the prepared urea-pyrimidone-polyol copolymer, self-repairing promoter, reinforcing agent, toughening agent, water-retaining agent, coagulant, and drag reducer to the aluminate clinker cementitious material, thereby realizing a simple, low-cost, self-repairing grouting material based on urea-pyrimidone suitable for large-deformation coal lanes in coal mines with self-repairing properties. In addition, because the urea-pyrimidone-polyol copolymer has multiple hydrogen bonds, when the material is damaged, the reversible dynamic hydrogen bonds will break before ordinary covalent bonds due to their weaker bond energy, and then under certain conditions, these reversible dynamic hydrogen bonds can rebond on the fracture surface to repair the damage, showing self-repairing properties, which is beneficial to improving the physical performance of the grouting joint.
[0034] According to another purpose of the present application, a self-healing grouting material based on urea-pyrimidone is proposed, which includes 7-10 parts of urea-pyrimidone-polyol copolymer, 1-3 parts of self-healing accelerator, 5-15 parts of auxiliary agent and 100 parts of cementitious material, calculated by mass; the cementitious material is aluminate clinker.
[0035] Among them, this embodiment proposes a self-repairing grouting material based on ureidopyrimidone, which includes 7-10 parts of ureidopyrimidone-polyol copolymer, 1-3 parts of self-repairing accelerator, 5-15 parts of auxiliary agent and 100 parts of cementitious material, in parts by mass; the cementitious material is aluminate clinker; the ureidopyrimidone-polyol copolymer is prepared by adding monomers composed of 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine to a mixed solution composed of lysine diisocyanate and dicyclohexylmethane diisocyanate, and then adding the mixed polyol, reacting at 90-100°C for 50-60min under a composite catalyst and a protective atmosphere, and then filtering and drying. The specific steps are obtained by referring to the method in the above embodiment and will not be repeated here. In addition, the self-repairing accelerator in this embodiment includes 4-pyrimidone, triazole pyrimidone and trifluorophenylpyrimidine in a mass ratio of 2:3:1; the auxiliary agent includes 2 parts of accelerator, 1 part of water retaining agent and 0.5 part of expansion agent in terms of mass parts, wherein the selection of accelerator, water retaining agent and expansion agent is referred to the above embodiment and will not be repeated here.
[0036] According to another object of the present application, it is proposed to use the self-repairing grouting material in any of the above embodiments in the self-repair of a large deformation coal lane in a coal mine.
[0037] The following is a specific example of the preparation method of the ureidopyrimidone-based self-repairing grouting material.
[0038] Example 1
[0039] Preparation of ureidopyrimidone-polyol copolymer: weigh 12 kg of 2-ureido-4[H]-pyrimidone and 3 kg of 4-dimethylaminopyridine monomers according to mass fractions, add them to 10 kg of mixed solution; wherein the mixed solution is a mixture of lysine diisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1:2; after the mixed solution and the monomers are mixed, auxiliary heating is performed to 35°C, stirring for 5 minutes to promote uniform mixing to obtain a uniform solution. 1 kg of composite catalyst is added to the obtained uniform solution, wherein the composite catalyst includes lithium chloride and 8-hydroxyquinoline copper in a mass ratio of 2:1, and then 3 kg of tetrahydrofuran diol and 9 kg of polypropylene glycol are added to the mixed polyol, and the reaction is carried out at 90°C for 60 minutes under the composite catalyst and protective atmosphere, and then the reaction solution is filtered and dried to obtain ureidopyrimidone-polyol copolymer.
[0040] Prepare 3 kg of self-repair accelerator by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0041] Prepare 15 kg of additives by mixing 5 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0042] Prepare 125 kg of self-repairing grouting material: weigh 7 kg of ureidopyrimidone-polyol copolymer, 3 kg of self-repairing accelerator and 15 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are as follows:
[0043] Grouting material self-repair surface crack healing rate: 94%;
[0044] Grouting material self-repair strength recovery rate: 82%;
[0045] Flexural strength of grouting material: 9.5MPa.
[0046] Compressive strength of grouting material: 55MPa.
[0047] Example 2
[0048] Compared with Example 1, in the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 91° C. for 55 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0049] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0050] Prepare 14 kg of additives by mixing 4 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0051] Prepare 122 kg of self-repairing grouting material: weigh 7 kg of ureidopyrimidone-polyol copolymer, 1 kg of self-repairing accelerator and 14 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are as follows:
[0052] Grouting material self-repair surface crack healing rate: 91%;
[0053] Grouting material self-repair strength recovery rate: 86%;
[0054] Flexural strength of grouting material: 9.8MPa;
[0055] Compressive strength of grouting material: 57MPa.
[0056] Example 3
[0057] Compared with Example 1, the process of preparing the ureidopyrimidone-polyol copolymer in this example is the same and will not be repeated herein.
[0058] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0059] Prepare 10 kg of additives by mixing 1 part of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 2 parts of coagulant and 2 parts of drag reducing agent;
[0060] Prepare 119 kg of self-repairing grouting material: weigh 8 kg of ureidopyrimidone-polyol copolymer, 1 kg of self-repairing accelerator and 10 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are as follows;
[0061] Grouting material self-repair surface crack healing rate: 97%;
[0062] Grouting material self-repair strength recovery rate: 89%;
[0063] Flexural strength of grouting material: 10.3MPa;
[0064] Compressive strength of grouting material: 60MPa.
[0065] Example 4
[0066] Compared with Example 1, in the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 93° C. for 58 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0067] Prepare 3 kg of self-repair accelerator by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0068] Prepare 13 kg of additives by mixing 4 parts of reinforcing agent, 2 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0069] Prepare 122 kg of self-repairing grouting material: weigh 8 kg of ureidopyrimidone-polyol copolymer, 1 kg of self-repairing accelerator and 13 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and test the product quality indicators as follows;
[0070] Grouting material self-repair surface crack healing rate: 96%;
[0071] Grouting material self-repair strength recovery rate: 91%;
[0072] Flexural strength of grouting material: 10.6MPa;
[0073] Compressive strength of grouting material: 62MPa.
[0074] Example 5
[0075] This example refers to Example 1 in the process of preparing the ureidopyrimidone-polyol copolymer.
[0076] Prepare 3 kg of self-repair accelerator by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0077] Prepare 12 kg of additives by mixing 4 parts of reinforcing agent, 2 parts of toughening agent, 1 part of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0078] Prepare 124 kg of self-repairing grouting material: weigh 9 kg of ureidopyrimidone-polyol copolymer, 2 kg of self-repairing accelerator and 12 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are as follows;
[0079] Grouting material self-repair surface crack healing rate: 98%;
[0080] Grouting material self-repair strength recovery rate: 93%;
[0081] Flexural strength of grouting material: 11.4MPa;
[0082] Compressive strength of grouting material: 66MPa.
[0083] Example 6
[0084] Compared with Example 1, in the process of preparing the ureidopyrimidone-polyol copolymer in this example, the reaction was carried out at 95° C. for 55 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0085] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0086] Prepare 7 kg of additives by mixing 1 part of reinforcing agent, 2 parts of toughening agent, 1 part of water retaining agent, 1 part of coagulant and 2 parts of drag reducing agent;
[0087] Prepare 118 kg of self-repairing grouting material: weigh 9 kg of ureidopyrimidone-polyol copolymer, 2 kg of self-repairing accelerator and 7 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are as follows;
[0088] Grouting material self-repair surface crack healing rate: 90%;
[0089] Grouting material self-repair strength recovery rate: 91%;
[0090] Flexural strength of grouting material: 10.1MPa;
[0091] Compressive strength of grouting material: 57MPa.
[0092] Example 7
[0093] Compared with Example 1, in the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 96° C. for 52 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0094] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0095] Prepare 6 kg of additives by mixing 1 part of reinforcing agent, 2 parts of toughening agent, 1 part of water retaining agent, 1 part of coagulant and 1 part of drag reducing agent;
[0096] Prepare 119 kg of self-healing grouting material: weigh 10 kg of urea-pyrimidone-polyol copolymer, 3 kg of self-healing accelerator and 6 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0097] Grouting material self-repair surface crack healing rate: 96%;
[0098] Grouting material self-repair strength recovery rate: 92%;
[0099] Flexural strength of grouting material: 12.1MPa;
[0100] Compressive strength of grouting material: 68MPa.
[0101] Example 8
[0102] Compared with Example 1, in the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 97° C. for 53 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0103] Prepare 3 kg of self-repair accelerator by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0104] Prepare 5 kg of additives by mixing 1 part of reinforcing agent, 1 part of toughening agent, 1 part of water retaining agent, 1 part of coagulant and 1 part of drag reducing agent;
[0105] Prepare 118 kg of self-healing grouting material: weigh 10 kg of urea-pyrimidone-polyol copolymer, 3 kg of self-healing accelerator and 5 kg of auxiliary agent, add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0106] Grouting material self-repair surface crack healing rate: 97%;
[0107] Grouting material self-repair strength recovery rate: 90%;
[0108] Flexural strength of grouting material: 10.8MPa;
[0109] Compressive strength of grouting material: 55MPa.
[0110] Example 9
[0111] Compared with Example 1, in the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 98° C. for 51 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0112] Prepare 3 kg of self-repair accelerator by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0113] Prepare 8 kg of additives by mixing 2 parts of reinforcing agent, 1 part of toughening agent, 1 part of water retaining agent, 3 parts of coagulant and 1 part of drag reducing agent;
[0114] Prepare 120 kg of self-healing grouting material: weigh 10 kg of urea-pyrimidone-polyol copolymer, 2 kg of self-healing accelerator and 8 kg of auxiliary agent, add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0115] Grouting material self-repair surface crack healing rate: 95%;
[0116] Grouting material self-repair strength recovery rate: 90%;
[0117] Flexural strength of grouting material: 10.6MPa;
[0118] Compressive strength of grouting material: 60MPa.
[0119] Example 10
[0120] Compared with Example 1, in the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 98° C. for 51 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0121] Prepare 3 kg of self-repair accelerator by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0122] Prepare 9 kg of additives by mixing 2 parts of reinforcing agent, 3 parts of toughening agent, 1 part of water retaining agent, 2 parts of coagulant and 1 part of drag reducing agent;
[0123] Prepare 118 kg of self-healing grouting material: weigh 7 kg of urea-pyrimidone-polyol copolymer, 2 kg of self-healing accelerator and 9 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0124] Grouting material self-repair surface crack healing rate: 93%;
[0125] Grouting material self-repair strength recovery rate: 89%;
[0126] Flexural strength of grouting material: 10.2MPa;
[0127] Compressive strength of grouting material: 65MPa.
[0128] Embodiment 11
[0129] Compared with Example 1, in the present example, during the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 100° C. for 50 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0130] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0131] Prepare 11 kg of additives by mixing 2 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 1 part of drag reducing agent;
[0132] Prepare 120 kg of self-healing grouting material: weigh 8 kg of urea-pyrimidone-polyol copolymer, 1 kg of self-healing accelerator and 11 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0133] Grouting material self-repair surface crack healing rate: 93%;
[0134] Grouting material self-repair strength recovery rate: 91%;
[0135] Flexural strength of grouting material: 11.0MPa;
[0136] Compressive strength of grouting material: 62MPa.
[0137] Example 12
[0138] Compared with Example 1, in the present example, during the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 100° C. for 55 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0139] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0140] Prepare 11 kg of additives by mixing 3 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 2 parts of coagulant and 1 part of drag reducing agent;
[0141] Prepare 123 kg of self-healing grouting material: weigh 9 kg of urea-pyrimidone-polyol copolymer, 3 kg of self-healing accelerator and 11 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0142] Grouting material self-repair surface crack healing rate: 94%;
[0143] Grouting material self-repair strength recovery rate: 91%;
[0144] Flexural strength of grouting material: 10.8MPa;
[0145] Compressive strength of grouting material: 61MPa.
[0146] Embodiment 13
[0147] Compared with Example 1, in the present example, during the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 100° C. for 55 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0148] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0149] Prepare 10 kg of additives by mixing 4 parts of reinforcing agent, 2 parts of toughening agent, 1 part of water retaining agent, 1 part of coagulant and 2 parts of drag reducing agent;
[0150] Prepare 122 kg of self-healing grouting material: weigh 10 kg of urea-pyrimidone-polyol copolymer, 2 kg of self-healing accelerator and 10 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0151] Grouting material self-repair surface crack healing rate: 99%;
[0152] Grouting material self-repair strength recovery rate: 96%;
[0153] Flexural strength of grouting material: 11.9MPa;
[0154] Compressive strength of grouting material: 71MPa.
[0155] Embodiment 14
[0156] Compared with Example 1, in the present example, during the process of preparing the ureidopyrimidone-polyol copolymer, the reaction was carried out at 100° C. for 55 min, and then the reaction solution was filtered and dried to obtain the ureidopyrimidone-polyol copolymer.
[0157] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0158] Prepare 7 kg of additives by mixing 1 part of reinforcing agent, 2 parts of toughening agent, 1 part of water retaining agent, 1 part of coagulant and 2 parts of drag reducing agent;
[0159] Prepare 118 kg of self-repairing grouting material: weigh 10 kg of urea-pyrimidone-polyol copolymer, 1 kg of self-repairing accelerator and 7 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes to obtain the self-repairing grouting material, and test the product quality indicators as follows.
[0160] Grouting material self-repair surface crack healing rate: 91%;
[0161] Grouting material self-repair strength recovery rate: 87%;
[0162] Flexural strength of grouting material: 10.5MPa;
[0163] Compressive strength of grouting material: 59MPa.
[0164] Embodiment 15
[0165] Compared with Example 1, the process of preparing the ureidopyrimidone-polyol copolymer in this example is the same and will not be repeated here.
[0166] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0167] Prepare 12 kg of additives by mixing 2 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0168] Prepare 123 kg of self-healing grouting material: weigh 8 kg of urea-pyrimidone-polyol copolymer, 3 kg of self-healing accelerator and 12 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0169] Grouting material self-repair surface crack healing rate: 94%;
[0170] Grouting material self-repair strength recovery rate: 90%;
[0171] Flexural strength of grouting material: 10.7MPa;
[0172] Compressive strength of grouting material: 58MPa.
[0173] Comparative Example 1
[0174] This comparative example refers to Example 1 in the process of preparing the ureidopyrimidone-polyol copolymer.
[0175] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0176] Preparation of 111 kg of self-repairing grouting material: weigh 9 kg of ureidopyrimidone-polyol copolymer and 2 kg of self-repairing accelerator and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes to obtain the self-repairing grouting material. The product quality indicators are as follows:
[0177] Grouting material self-repair surface crack healing rate: 96%;
[0178] Grouting material self-repair strength recovery rate: 90%;
[0179] Flexural strength of grouting material: 9.3MPa;
[0180] Compressive strength of grouting material: 47MPa.
[0181] Comparative Example 2
[0182] In the process of preparing the ureidopyrimidone-polyol copolymer in this comparative example, the composite catalyst includes lithium chloride and 8-hydroxyquinoline copper in a mass ratio of 2:1, and 12 kg of tetrahydrofuran diol is added. Other features refer to Example 1.
[0183] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0184] Prepare 12 kg of additives by mixing 2 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0185] Prepare 123 kg of self-healing grouting material: weigh 8 kg of urea-pyrimidone-polyol copolymer, 3 kg of self-healing accelerator and 12 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0186] Grouting material self-repair surface crack healing rate: 78%;
[0187] Grouting material self-repair strength recovery rate: 63%;
[0188] Flexural strength of grouting material: 9.3MPa;
[0189] Compressive strength of grouting material: 46MPa.
[0190] Comparative Example 3
[0191] This comparative example refers to Example 1 in the process of preparing the ureidopyrimidone-polyol copolymer.
[0192] Prepare 15 kg of additives by mixing 5 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0193] Prepare 124 kg of self-repairing grouting material: weigh 9 kg of urea-pyrimidone-polyol copolymer and 15 kg of additives and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0194] Grouting material self-repair surface crack healing rate: 72%;
[0195] Grouting material self-repair strength recovery rate: 69%;
[0196] Flexural strength of grouting material: 8.9MPa;
[0197] Compressive strength of grouting material: 43MPa.
[0198] Comparative Example 4
[0199] This comparative example refers to Example 1 in the process of preparing the ureidopyrimidone-polyol copolymer.
[0200] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0201] Prepare 12 kg of additives by mixing 5 parts of enhancer, 2 parts of water retainer, 3 parts of coagulant and 2 parts of drag reducer;
[0202] Prepare 122 kg of self-healing grouting material: weigh 7 kg of urea-pyrimidone-polyol copolymer, 3 kg of self-healing accelerator and 12 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0203] Grouting material self-repair surface crack healing rate: 84%;
[0204] Grouting material self-repair strength recovery rate: 76%;
[0205] Flexural strength of grouting material: 8.8MPa;
[0206] Compressive strength of grouting material: 43MPa.
[0207] Comparative Example 5
[0208] This comparative example refers to Example 1 in the process of preparing the ureidopyrimidone-polyol copolymer.
[0209] 3 kg of self-repair accelerator is prepared by mixing 1 kg of 4-pyrimidone, 1.5 kg of triazole pyrimidone and 0.5 kg of trifluorophenylpyrimidine;
[0210] Prepare 15 kg of additives by mixing 5 parts of reinforcing agent, 3 parts of toughening agent, 2 parts of water retaining agent, 3 parts of coagulant and 2 parts of drag reducing agent;
[0211] Prepare 118 kg of self-healing grouting material: weigh 3 kg of urea-pyrimidone-polyol copolymer, 3 kg of self-healing accelerator and 12 kg of auxiliary agent and add them to 100 kg of aluminate clinker, mix them in a dry powder mixer for 20 minutes, and the product quality indicators are tested as follows.
[0212] Grouting material self-repair surface crack healing rate: 79%;
[0213] Grouting material self-repair strength recovery rate: 72%;
[0214] Flexural strength of grouting material: 9.7MPa;
[0215] Compressive strength of grouting material: 41MPa.
[0216] It should be noted that, in the description of this application, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. In addition, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0217] Any process or method description in a flowchart or otherwise described herein may be understood to represent a module, segment or portion of code that includes one or more executable instructions for implementing the steps of a specific logical function or process, and the scope of the preferred embodiments of the present application includes alternative implementations in which functions may not be performed in the order shown or discussed, including performing functions in a substantially simultaneous manner or in the reverse order depending on the functions involved, which should be understood by technicians in the technical field to which the embodiments of the present application belong.
[0218] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0219] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a self-repairing grouting material based on ureidopyrimidone, characterized in that: The steps include: The monomers composed of 2-ureido-4[H]-pyrimidone and 4-dimethylaminopyridine in a mass ratio of 4:1 are added to a mixed solution composed of lysine diisocyanate and dicyclohexylmethane diisocyanate in a mass ratio of 1:2, and then a mixed polyol composed of tetrahydrofuran diol and polypropylene glycol in a mass ratio of 1:3 is added, and the mixture is reacted at 90-100° C. for 50-60 minutes under a composite catalyst and a protective atmosphere, and then the reaction solution is filtered and dried to obtain a ureido pyrimidone-polyol copolymer; wherein the mass ratio of the monomer to the mixed solution is 3:2; the mass ratio of the composite catalyst to the monomer is 1:15; and the mass ratio of the mixed polyol to the monomer is 4:5; In parts by mass, 7-10 parts of the ureidopyrimidone-polyol copolymer, 1-3 parts of the self-repairing accelerator and 5-15 parts of the auxiliary agent are added to 100 parts of the cementitious material, and the dry powder is stirred to obtain the self-repairing grouting material.
2. The preparation method according to claim 1, characterized in that: The composite catalyst comprises lithium chloride and 8-hydroxyquinoline copper in a mass ratio of 2:
1.
3. The preparation method according to claim 2, characterized in that: The self-repairing accelerator comprises 4-pyrimidone, triazole pyrimidone and trifluorophenylpyrimidine in a mass ratio of 2:3:
1.
4. The preparation method according to claim 2, characterized in that: Calculated by weight, the additives include 1-5 parts of a reinforcing agent, 1-3 parts of a toughening agent, 1-2 parts of a water retaining agent, 1-3 parts of a coagulant, and 1-2 parts of a drag reducing agent.
5. The preparation method according to claim 2, characterized in that: The cementitious material is aluminate clinker.
6. A self-repairing grouting material based on ureidopyrimidone, characterized in that: It is obtained by the preparation method described in any one of claims 1 to 5, and comprises, by weight, 7-10 parts of ureidopyrimidone-polyol copolymer, 1-3 parts of self-repairing accelerator, 5-15 parts of auxiliary agent and 100 parts of cementitious material; the cementitious material is aluminate clinker.
7. The self-repairing grouting material according to claim 6, characterized in that: The self-repairing accelerator comprises 4-pyrimidone, triazole pyrimidone and trifluorophenylpyrimidine in a mass ratio of 2:3:
1.
8. The self-repairing grouting material according to claim 6, characterized in that: Calculated by weight, the additives include 1-5 parts of a reinforcing agent, 1-3 parts of a toughening agent, 1-2 parts of a water retaining agent, 1-3 parts of a coagulant, and 1-2 parts of a drag reducing agent.
9. Application of the self-repairing grouting material according to any one of claims 6 to 8 in the self-repair of a large deformation coal lane in a coal mine.
Citation Information
Patent Citations
Wear-resistant self-repairing polyurethane composite coating agent based on shape memory and preparation method thereof
CN113214450A
Cement-polyurethane composite grouting material suitable for reinforcing compact soft rock and preparation method of cement-polyurethane composite grouting material
CN117585952A